Rancang Bangun Sistem Informasi Skrining Kesehatan Mandiri Berbasis Web Menggunakan Quick Response (QR) Code di Klinik Mandiri Dokter Iqbal Kurniawan - Abdul Rachman Tuatoy; Guntur Virghiawan Soekarno; Muhammad Wildan Shubhan; Afiani Agus Abdillah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Currently, the health screening process at Klinik Mandiri Dr. Iqbal Kurniawan is still conducted manually, resulting in inefficiency, the risk of recording errors, and challenges in patient data management. This study aims to design and develop a web-based Health Screening Information System integrated with Quick Response Code (QR Code) technology to improve service efficiency. The system development method utilizes the XAMPP local server, while data collection was carried out through observation, interviews, and literature study. The main features of the system include patient registration via QR code scanning, online self-screening form submission, and centralized data management accessible by administrators via a dashboard. The test results demonstrate that the system successfully accelerates the administrative process, minimizes human error in recording, and optimizes patient data storage. The implementation of this system is expected to modernize the health service workflow at the clinic, create more accurate and integrated data management, and enhance the overall quality of service for patients.